Puss in boots - Perrault, Charles 1628-1703.; Marcellino, Fred.; Arthur, Malcolm (New York Farrar Straus Giroux, 1990)
A retelling of the French fairy tale in which a clever cat wins his master a fortune and the hand of a princess.
Translation of: Le chat botte.
"A Sunburst book."
"Caldecott honor book."--Cover.
Keywords: Fairy tales; Folklore -- France